Involvement of Membrane Progestin Receptor Beta (mPRβ/Paqr8) in Sex Pheromone Progestin-Induced Expression of Luteinizing Hormone in the Pituitary of Male Chinese Black Sleeper (Bostrychus Sinensis) - Zhang, Yu Ting; Hong, Wan Shu; Liu, Dong Teng; Qiu, Heng Tong; Zhu, Yong; Chen, Shi Xi (Frontiers in Endocrinology, 2018)
Our previous studies showed that 17α, 20β-dihydroxy-4-pregnen-3-one (DHP) acted as a sex pheromone to induce reproductive success in Chinese black sleeper (Bostrychus sinensis), but its functional mechanism remains unclear. In the present study, we cloned the cDNAs of the gonadotropin subunits (cgα, fshβ and lhβ), and found that, in exposure to 5 nM DHP, transcript of lhβ significantly increased in the pituitary at 6h post exposure; plasma 11-KT level increased at 24h post exposure in mature male fish. In contrast, DHP exposure failed to increase the transcript of lhβ in the pituitary of immature male fish, suggesting that the responsiveness to DHP depends on reproductive status. Interestingly, expression of progestin and adipoQ receptor 8 (paqr8, also known as mPRβ) and progestin receptor membrane component 2 significantly increased in the olfactory rosette of male fish at late meiotic stage following a co-injection of human chorionic gonadotropin (HCG) and luteinizing hormone releasing hormone-A3 (LHRH-A3), while no increases of other progestin receptors were observed. Moreover, Paqr8 protein was localized in the dendritic knobs of the olfactory sensory neurons, which were activated following the in vivo exposure to DHP. The DHP-induced expression of lhβ in pituitary was not inhibited by RU486, an antagonist of nuclear progesterone receptor. Taken together, our results suggested that sex pheromone DHP increased the expression of lhβ transcript in the pituitary and plasma 11-KT levels of mature male, important for reproduction; and Paqr8 might be involved in responding to sex pheromone DHP in the olfactory rosette of male B. sinensis.